The Friction and Wear Properties of Metal-Doped DLC Films under Current-Carrying Condition. Issue 6 (2nd November 2019) - Wang, Yunfeng; Wang, Yan; Li, Xia; Li, An; Lu, Zhibin; Zhang, Guangan; Wu, Zhiguo
Abstract: In an effort to improve the surface properties of electrical contact materials in terms of high friction coefficient and wear rate, diamond-like carbon (DLC) films containing different metal elements were prepared on stainless steel substrates using an unbalanced magnetron sputtering system. In the present study, the effect of current-carrying on DLC film, Cu-doped DLC film (Cu/DLC), and Ti-doped DLC film (Ti/DLC) is reported. The structure and mechanical properties of the films were characterized systematically by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and Raman spectra; these methods were also used to analyze the initial surface of the films. Moreover, the tribological behaviors of the films sliding against AISI 52100 steel with and without an electric current (1 A) applied were investigated using a tribometer with ball-on-disc configuration in an atmospheric environment. The results demonstrated that the friction coefficients of DLC and Cu/DLC under current-carrying condition were decreased, whereas Ti/DLC showed opposite experimental results. The wear rate of the films with a current was higher than that without a current. Therefore, this study is meaningful to understand the tribological behaviors of microelectromechanical systems.